2010
DOI: 10.1055/s-0030-1265286
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Thromboelastography: One Size Does Not Fit All

Abstract: Coagulation management requires the balancing of different components that contribute to clot formation. These components include the interactions between platelets, procoagulant, anticoagulant, and fibrinolytic factors. The cause of bleeding or thrombotic events is often multifactorial; however, the tests clinicians most frequently use to assess hemostasis do not reflect the complexity of the coagulation system. The paucity of global measurements of hemostasis has resulted in either an empirical or a one-size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 109 publications
0
45
0
Order By: Relevance
“…There was a clear advantage for ROTEM as compared to standard coagulation test concerning extensively shorter turnaround times, which will have impact on a timely and more targeted coagulation therapy [30][31][32].…”
Section: Management Of Dilutional Coagulopathy In Childrenmentioning
confidence: 99%
“…There was a clear advantage for ROTEM as compared to standard coagulation test concerning extensively shorter turnaround times, which will have impact on a timely and more targeted coagulation therapy [30][31][32].…”
Section: Management Of Dilutional Coagulopathy In Childrenmentioning
confidence: 99%
“…Second, we did not concurrently examine standard coagulation parameters in parallel with TEG. Prior studies have demonstrated that TEG out-performs traditional laboratory testing for coagulation abnormalities [19,41], TEG better predicts outcomes compared to traditional tests [8,20], and TEG may be more cost-effective [42]. Therefore, we did not feel that further comparison with standard coagulation parameters was necessary.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, TEG may help document the prothrombotic state that sometimes occurs in post liver transplant patients because of deficiencies in antithrombin Ⅲ and protein C causing potentially disastrous hepatic artery thrombosis [56] . Even though the usefulness of TEG in complex coagulation defects has been questioned [57] , recent literature does reaffirm that the use of TEG and rotation thromboelastometry in more rational transfusion algorithms can reduce the number of blood products transfused [58] .…”
Section: Thromboelastographymentioning
confidence: 99%